WTO Financial Services Commitments : Determinants and Impacton Financial Stability - Valckx, Nico (IMF Working Papers; Working Paper ;, 2002)
The paper investigates the factors that have influenced WTO members to take on their chosen level of liberalization commitments in the framework of liberalization of trade in financial services and the impact of such commitments on financial sector stability. The most important factors are economic growth, current account, trends in banking sector development, policy restrictiveness, and peer group effects. The econometric evidence suggests that more liberal commitments may be associated with greater vulnerability to currency and banking crises-most likely a short-term effect, which should be mitigated with time through increased market efficiency and better resource allocation.